Evaluation of Conditions for Self-Healing of Additively Manufactured Polymer Composites with Continuous Carbon Fiber Reinforcement - Marius Rimašauskas; Tomas Kuncius; Rūta Rimašauskienė; Tomas Simokaitis (Journal of Manufacturing and Materials Processing, 2025)
Additive manufacturing (AM) is one of the most frequently used technologies to produce complex configuration products. Moreover, AM is very well known as a technology which is characterized by a low amount of generated waste and the potential to be called zero-waste technology. As is known, there are seven main groups of technologies described in the ISO/ASTM 52900 standard that allow the use of very different materials from polymers to metals, ceramics, and composites. However, the increased utilization of additively manufactured composites for different applications requires a deeper analysis of production processes and materials’ characteristics. Various AM technologies can be used to produce complex composite structures reinforced with short fibers; however, only material extrusion (MEX)-based technology is used for the production of composites reinforced with continuous fibers (CFs). At this time, five different methods exist to produce CF-reinforced composite structures. This study focuses on co-extrusion with the towpreg method. Because of the complexity and layer-by-layer nature of the process, defects can occur during production, such as poor interlayer adhesion, increased porosity, insufficient impregnation, and others. To eliminate or minimize defects’ influence on mechanical properties and structural integrity of additively manufactured structures, a hypothesis was proposed involving heat treatment. Carbon fiber’s conductive properties can be used to heal the composite structures, by heating them up through the application of electric current. In this research article, an experimental evaluation of conditions for additively manufactured composites with continuous carbon fiber reinforcement for self-healing processes is presented. Mechanical testing was conducted to check the influence of heat treatment on the flexural properties of the composite samples.